Case Study of Recruitment and Selection of Employees in the Family Businesses of Tasikmalaya - Dedi Rianto Rahadi; Pandu Cakranegara; Genoveva Claudia (Faculty of Business, President University, 2018)
Human resource planning within a company includes policies such as recruitment and selection, compensation, performance appraisal, career development, and training and development. Recruitment and selection process becomes the main factor to do professional human resources. The purpose of this research is to know how the concept of recruitment and selection model on family business in small and medium enterprise sector. The object of research is small and medium business in Tasikmalaya city in handicraft sector. The research method used qualitative and data collection through triangulation method where researchers examine the interrelated phenomena from different perspectives. The results showed that family emotional relationship factors often affect the recruitment and selection process of employees. Moreover, Incompetent recruitment and selection models will threaten the performance and even the existence of the company. The poor management of human resources in the family company will have negative impacts such as the outbreak of conflict, the unfavourable working situation, the development of various intrigues, and the high level of employee turnover will ultimately impact on the performance of the company.